Implementasi Employee Relations Dalam Meningkatkan Engagement Karyawan Di PT Pos Indonesia Kantor Cabang Utama Bandung - Aninditha, Aqmalina Putri; Hendriyani, Chandra; Rochmah, Tengku Sitti; Garnida, Agus (Akademi Sekretari Manajemen Taruna Bakti, 2023)
Human resources are the driving force of a company to achieve goals effectively and efficiently. Harmonization of the relationship between management and employees needs to be fostered and improved from time to time. PT Pos Indonesia as a government-owned company developed a strategy in the form of implementing a number of employee relations activities to increase employee engagement. The research method used is a descriptive qualitative method obtained through field observations and literature studies. The results showed that the employee relations activities planned by PT Pos Indonesia were in the form of education and training programs, award programs, and special events programs that could increase employee performance and engagement with the company. The largest participation in employee relations activities is a special program, while the most influential dimension of employee engagement is the Vigor dimension, which is the delivery of energy from employees to do their work with enthusiasm and willingness. Other positive impacts that are felt directly by employees have increased work motivation, a sense of respect, a positive work climate, and high loyalty.